Antimicrobial Activities of Aqueous and Methanolic Extracts from Salvia officinalis and Salix acmophylla Used in the treatment of wound infection isolates - Ali, M.R.; Aboud, A.S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aqueous and methanol extracts of Salvia officinals and Salix acmoplylla traditionally used for the treatment of infections disease were tested for their active against gram positive and gram negative bacteria isolated from wound infection culture using the broth dilution and disc diffusion melhod. Results of this study revealed the prescence of phytochemical which were active against gram positive and negative bacteria. Methanol extracts of both plants showed the highest activity other the aqueous extract. The minimum inhibitory concentration (MIC) of the aqueous extracts on the test organism was 25- 100 mg,while that of the methanol extract was ranged between 25 -50 mgon the test organisms, the minimum bacterial concentration (MBC) ranging between 25-100 mgfor methanol extract , and 25-200 mgfor aqueous extracts. The highest activity at 100 and 121 oC was demonstrated by the methanol extracts of Salix acmophylla against Staphylococcus aureus and Klebsiella spp. While in methanol extracts of Salvia officinalis the 45 oC was the effective temperature. In this study plants extracts against gram negative bacteria showed activity in acidic pH only in contrast of gram positive bacteria which were constant in all plants extract . Salvia officinalis contained essential elements at higher levels than Salix acmoplylla .Ca and Zn were present of high levels in Salix acmoplylla than other. The results of this study suggest the possibility of using the methanolic extracts of these plants in treating diseases caused by the test organisms, especially when prepared at acidic pH.